King's cross : the story of the world in the life of Jesus - Keller, Timothy, 1950- (New York, N.Y. : Dutton Redeemer, 2011)
Presents a revelatory examination of the life of Christ as told in the Gospel of Mark, inviting readers to review their personal relationships with God with a greater understanding of historical events.
pt. 1. The King. The dance -- The call -- The healing -- The rest -- The power -- The waiting -- The stain -- The approach -- The turn -- pt. 2. The cross. The mountain -- The trap -- The ransom -- The temple -- The feast -- The cup -- The sword -- The end -- The beginning.
Includes bibliographical references (p. 231-236).
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Bible. -- Criticism, interpretation, etc